The Effect of Various Types of Natural Sweeteners in Agar with Rice Bran Addition on Organoleptic and Physicochemical Characteristics - Suseno, Rahayu; Marcelina, Bangun Naomi; Rahmi, Silvi Leila (Indonesian Food Science and Technology Journal, 2019)
Abstract— This research was conducted in two stages, first stage, looking for the best concentration of natural sweetener with organoleptic. Second stage analyzed the physicochemical characteristics using the best concentration of first stage. This research was carried out using a Completely Randomized Design, with various natural sweeteners consisting 6 levels, namely: stevia sweetener (0.05%, 0.75%, 0.10%), sorghum sugar (10%, 15%, 20%), corn sugar (10%, 15%, 20%), coconut sugar (14%, 15%, 16%), palm sugar (7.5%, 10%, 12.5%), and honey (15%, 25%, 35%) and 3 replications so that 18 experimental units. The addition of various types of natural sweeteners significantly affected the hedonic test (taste and overall acceptance), water content, pH, total dissolved solids, total sugar, and color but did not significantly affect the hedonic quality test (texture), hedonic test (texture and color), crude fiber content, syneresis and gel hardness. Keywords— Agar, Natural Sweeteners, Rice Bran